Effect of Product Attribute Performance and Customer Relationship Management, To Customer Segment Industrial Fabrics textile in Java - ARIEF WIDYARTO; YUYUS SURYANA; MEYDIA HASAN (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
The company producing textile fabrics in Java face the problem of the level of the segment of business customers for the products of local production of textile fabrics which tend to be relatively low. The situation is suspected because of the performance attributes of the product and Customer Relationship Management developed by the company is still not optimal. The research objective is to obtain results of a study on the performance of the product attributes and the implementation of Customer Relationship Management and its influence on the level of customer share of textile fabric products in the area of Java. The method used is descriftive and explanatory method. The unit of analysis is the company’s textile fabric industry in Java. Time horizon is a cross-sectional, where research is done in one time simultaneously. Data collected from a questionnaire to retailers of textiles and interviews with the managers and interviews mendalamdengan several national textile practitioners. Data were analyzed descriptively and quantitatively. Testing the hypothesis through the PLS model (Partial Least Square). The findings indicate that the performance attributes of the product and Customer Relationship Management developed by the company textile fabric in Java has not been good, resulting in the customer segment level is still low. The conclusion of the study is that the contribution of the performance attributes of the product is more dominant than the Customer Relationship Management on the level of customer segment.Keywords: Performance Product Attributes, Customer Relationship Management, customer segment